Neuroimaging in Neurocutaneous Syndromes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The radiographic manifestations of neurocutaneous syndromes are reviewed from the Albert Einstein College of Medicine/Montefiore Medical Center, Bronx, NY; and the University of New Jersey, Robert Wood Johnson Medical School, New Brunswick, NJ.